Permintaan Pariwisata Indonesia dari Tujuh Negara ASEAN Tahun 2005-2019 - Madeline Elfriede Pasaribu; Atik Maratis Suhartini (Politeknik Statistika STIS, 2021)
The tourism sector in Indonesia has considerable influence due to this sector as core economy, has enough high multiplier effect and its role as an invisible export. This sector is able to contribute more than 4 percent of income to national GDP and the foreign exchange that tends to increase. ASEAN region is one of the regions that brings most foreign tourists to Indonesia with positive trend during 2005-2019 period, but its growth fluctuative. This paper aims to analyze variables that influences tourism demand from ASEAN due to proximity in historical and geographical. Panel data regression analysis using FEM SUR estimation method shows that per capita income, oil prices and trade openness have a significant effect on increasing tourism demand from seven ASEAN countries to Indonesia. Meanwhile, the relative price has no significant effect on the tourism demand.